Strategic alliances and the rate of new product development: An empirical study of entrepreneurial biotechnology firms - Deeds, David L.; Hill, Charles W.L. (Journal of Business Venturing, 1996)
A key to success in industries populated by entrepreneurial high-technology firms is the rate at which the firm develops new products. Rapid product development creates significant advantages for entrepreneurial firms, including access to early cash flows, external visibility, legitimacy, and early market share. The higher a firm's rate of new product development, the more likely the firm is to achieve and maintain these first-mover advantages. This is particularly true in industries such as pharmaceuticals, where the effectiveness of patent protections leads to patent races in which a “winner take all” scenario exists. But even in industries where patent protection is weak, the advantages of being first, in terms of market preemption, reputation effects, experience curve effects, etc., can still be of major importance. We argue that one way an entrepreneurial firm can increase its rate of new product development is by entering into strategic alliances with firms that possess complementary assets. The basic proposition advanced is that a firm's rate of new product development is a positive function of the number of strategic alliances that it has entered. However, the relationship between strategic alliances and the rate of new product development may be nonlinear. Specifically, although strategic alliances may initially have positive effects on the rate of new product development, this relationship may exhibit diminishing returns. Moreover, past some point it is possible that negative returns may set in. Thus, the relationship between the number of alliances and the rate of new product development may be an inverted U-shape. Two reasons can be given to support such a relationship. First, not all alliances will make an equal contribution to increasing the rate of new product development. The economic “law” of diminishing returns suggests that the more alliances a firm engages in, the more likely it is to enter some alliances whose marginal contribution is relatively minor. Such a phenomenon on its own is enough to suggest diminishing returns. Second, gaining access to complementary assets through strategic alliances is not without risks. Malperformance may occur when the firm discovers that the complementary assets provided by the partner are a poor match, fail to live up to the promises made by the partner, or a partner may opportunistically exploit an alliance, expropriating the firm's know-how while providing little in return. These problems arise because the effectiveness with which the firm can select and manage alliance partners is likely to be negatively related to the number of alliances the firm is managing. Due to information processing requirements, the quality of partner search and the ability to monitor the partners' actions will decline as the firm increases the number of alliances in which it is involved. This reasoning leads to a prediction that past some point, alliances will be increasingly vulnerable to malperformance. This raises not only the possibility of diminishing returns to the number of alliances, but also negative returns as the number of alliances increases past some critical point. This proposed relationship between alliances and new product development was tested on a sample of 132 biotechnology firms. The results provide strong evidence to support the inverted U-shaped relationship between the number of strategic alliances and the rate of new product development. Therefore, at low levels strategic alliances are positively related to new product development, but as the number of alliances increases, the benefits begin to decrease, and at high levels the costs of an additional alliance actually outweigh the benefits.